Hubungan Pola Asuh Dengan Kejadian Temper Tantrum Pada Anak Toddler Di Asrama Militer Kabupaten Jembrana: THE RELATIONSHIP BETWEEN PARENTING PATTERNS AND THE INCIDENCE OF TEMPER TANTRUMS IN TODDLER CHILDREN AT THE MILITARY DORMITORY IN JEMBRANA REGENCY. - Yuningsih, Yuningsih (LPPM Universitas dr. Soebandi, 2024)
Temper tantrums are episodes of extreme anger and frustration, characterized by behavior such as crying, screaming, and violent or aggressive body movements, caused by factors such as physiological, psychological, parental, and environmental. The incidence of tantrums in Indonesia in 2019 increased to 1.52%. Based on a preliminary study conducted at the Jembrana Regency Military Dormitory, of 10 pre-school age children, it was found that 50% of the children experienced temper tantrums. The aim of this research was to determine the relationship between parenting patterns and the incidence of temper tantrums in toddler children in the Jembrana Regency Military Dormitory. The type of design is correlational with a cross sectional approach. The population in this study were all 42 mothers who had toddler children. The total sample of 42 mothers was taken using a saturated sampling technique. The instrument uses a parenting style questionnaire and a temper tantrum questionnaire. The research results showed that democratic parenting was 42.9% and the incidence of temper tantrums was low at 50.0%. Data analysis used the lambda test and correlation coefficient. The p-value obtained was 0.048 <α 0.05, so H0 was rejected and Ha was accepted, indicating that there was a significant relationship between parenting styles and the incidence of temper tantrums and an r value of 0.333 was obtained, which means the level of closeness of the relationship between the two variables is low. From the results of this research, it can be concluded that the better the parenting style applied to children, the smaller the occurrence of temper tantrums in children. Advice for parents is to apply good parenting patterns such as democratic parenting so that children do not easily experience excessive tantrums.